CEACAM6 is a prognostic biomarker and potential therapeutic target for gastric carcinoma - Ru, Guo-Qing (Oncotarget, 2017)
This study aims to investigate the prognostic power of carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) in gastric cancer (GC) and its potential role in cancer development and progression. Data mining results show that CEACAM6 is overexpressed in gastric cancer and is correlated with lymph node metastasis. Subsequently, immunohistochemical staining was performed to determine CEACAM6 protein levels in paraffin gastric tumor specimens. Real-time reverse-transcription-polymerase chain reaction (RT-PCR) was conducted to detect CEACAM6 mRNA levels in fresh GC samples. CEACAM6 protein and mRNA levels were significantly up regulated in GC compared with paired normal mucosa. The IHC staining intensity of CEACAM6 was positively correlated with tumor size, Lauren's classification, vascular invasion, lymph node metastasis, distant metastasis, and TNM stage. CEACAM6 expression was inversely correlated with the five-year survival rate of GC patients. Cox multivariate analysis results demonstrated that the overall survival was independently correlated with CEACAM6 expression. A significant association was observed between CEACAM6 and distant metastases. Network analysis of downstream gene signatures revealed several hub genes such as SRC and DNM1L etc. which may mediating tumor promoting functions of CEACAM6. Further data mining discovered that Tamoxifen etc. could be therapeutic alternatives for gastric patients with CEACAM6 overexpression. Collectively, CEACAM6 overexpression is a common characteristic of GC and is associated with poor 5 year survival rate in GC. Besides, potential molecular mechanisms and treatment options were also provided.